The ethanol extract of the bastard cedar (Guazuma ulmifolia L.) as antioxidants - Sijani Prahastuti; Meilinah Hidayat; Stella Tinia Hasiana; Wahyu Widowati; Wahyu Setia Widodo; Rr. Anisa Siwianti Handayani; Rizal Rizal; Hanna Sari Widya Kusuma (Universitas Ahmad Dahlan, 2020)
Guazuma ulmifolia, or commonly known as the bastard cedar, has many pharmaceutical activities and is, therefore, claimed as a source of various plant-based medicines. This reserach was purposed to identify the antioxidant activities of the ethanolic extract of G. ulmifolia (EEGU) by phytochemical screening assay, total flavonoid and total phenolic testing, and comparative analysis between the antioxidant activities of EEGU and epicatechin. The qualitative phytochemical screening assay of EEGU detected the availability of phenols, flavonoids, alkaloids, tannins, and terpenoids, but not saponins and triterpenoids. Meanwhile, the total phenolic content was 32.24 µg GAE/mg extract, and the total flavonoid content decided using aluminum chloride reagent with quercetin standard, was 6.48 µg QE/mg extract. The role of antioxidants examined by FRAP, DPPH, H2O2, and ABTS assays. These assay are proved that the IC50 values of EEGU are higher than those of epicatechin. For DPPH scavenging, H2O2 scavenging, and ABTS reduction activities, EEGU resulted IC50 45.70 μg/mL, 162.93 μg/mL, and 35.96 μg/mL, while epicatechin only yielded IC50 0.56 μg/mL, 57.91 μg/mL, and 16.74 μg/mL respectively. Otherwise, the highest reduction in FRAP activities were shown at 50 μg/mL concentration of epicatechin and EEGU were 236.33 and 202.71 µM Fe (II)/µg respectively. Based on these results, EEGU is concluded as an active natural product because it exhibit antioxidant activities.